Attempts to teach ethics to police leaders and managers at the Police College: a lesson from history - Adlam, Robert (Policing and society, 2024)
This practitioner and experience-based insider account outlines the reasons for the introduction in the late 1970s of a named ‘ethics package’ to the content of courses of study at the Police College, Bramshill. The context of the College, and the modal characteristics of its client groups of middle and senior ranking police officers are highlighted. In 1978 an ‘ethics package’ began to be constructed in order to make a significant contribution to the ‘professional’ knowledge and practices commensurate with the role-requirements of police leadership. An outline of the intellectual basis guiding and informing the content of the ‘ethics package’ is provided. The paper then identifies some of the persistent and often disappointing responses to the continuing attempts to include something called ‘ethics’ on the various programmes of study at Bramshill. From 1992 onwards ‘ethics’ was to make various appearances on the leadership and management courses but its status was always fragile partly because of the various regime changes that befell the institution. In 1994 a formal educational action-research process, was begun which sought to position ‘ethics’ on the ‘Police Management Programme’ such that the subject would not be set aside. However, after six years of commitment and endeavour, the feedback from course participants never achieved the level of positive response needed to achieve the fundamental aim of the research project. The paper concludes with a very brief summary of some of the reasons why presenting something called ‘ethics’ to experienced police officers was – and perhaps remains – intrinsically difficult.